PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU PADA SMK AL AMANAH AL BANTANI TANGERANG SELATAN - Finatariani, Endah; Purwatiningsih, Purwatiningsih; Astuti, Widiyanti Rahayu Budi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Functionally, teachers are the foundation for educational institutions, so good teacher performance indicates good school quality. Therefore, it is important to place teachers as potential resources, which in practice, schools are present as a forum for empowering and improving the quality of teachers, both in terms of knowledge, teaching competence, and personality. In fact, this study pays special attention to the phenomenon of teacher performance in terms of the principal's leadership role and work motivation. The research was conducted at one of the Islamic-based formal education institutions, namely SMK Al Amanah Al Bantani, South Tangerang. While the research subjects were teachers, totaling 52 people. In practice, this study uses a quantitative approach by distributing questionnaires as research instruments, while the analysis technique uses multiple linear regression statistical tests. The results of statistical tests conclude that teacher performance is a good behavior in teaching science and educating students, where teacher performance will increase as the motivation and leadership role of the principal increases. In fact, the results of the simultaneous test show that the most effective model for improving teacher performance is work motivation, especially enthusiasm in educating students to excel (success). This finding suggests that teachers have a strong intention to provide quality education. Then the school should be Al Amanah Al Bantani Vocational School can maximize this potential in order to achieve the goals of the institution.